User-generated insight of Rio's Rocinha favela tour: Authentic attraction or vulnerable living environment?. (November 2019) - Wise, Nicholas; Polidoro, Maurício; Hall, Gareth; Uvinha, Ricardo Ricci
Urban transformations help shape new opportunities and create/re-create awareness in everyday living environments. It is not transformation in the infrastructural sense, but transformation in the form of a service industry producing socio-economic change that can result in inclusion and exclusion of people in the community, thus affecting the everyday living environment. Within this, we need to consider the tourist gaze and how users who visit/tour vulnerable living environments report perceptions of their experiences on forums such as TripAdvisor, which helps researchers frame understandings of commodification, opportunities/awareness and even authenticity (each addressed in this paper). This paper evaluates TripAdvisor posts of 'Rio's Rocinha Favela Tour'. In many respects, the notion of commodification, and even authenticity, runs through each theme, but the analysis and data posted to TripAdvisor challenges us to consider how a favela becomes a consumer product or a tourist attraction. The Rocinha Favela tour is widely publicised to prospective visitors as a chance to experience a living and working favela, the focus of the first theme presented in this paper. Given Rocinha has become a popular attraction in Rio, this leads to the second theme: opportunity or awareness. Opportunities do exist for people in the community to get involved in tourism, and turning the favela into a product helps shape and maintain awareness. The third theme builds on and relates to the previous two, but focuses more on the semblances of authenticity that emerges. To link the points highlighted in this paper, a discussion of soft power concerns relationships bonded through economic and cultural influence. Because favelas have become distinct attractions, it is cultural appeal and a different (residential) side of the city that persuades travellers to visit. Online and social media platforms for more than a decade now have played an important role today in projecting images and promoting authentic experiences based on user-perceptions, and this paper looks at how the users communicate their experiences.